Activity of core modified 10-23 DNAzymes against HCV - Robaldo, Laura (2014)
The highly conserved untranslated regions of the hepatitis C virus (HCV) play a fundamental role in viral translation and replication and are therefore attractive targets for drug development. A set of modified DNAzymes carrying (2′R)-, (2′S)-2′-deoxy-2′-C-methyl- and -2′-O-methylnucleosides at various positions of the catalytic core were assayed against the 5′-internal ribosome entry site element (5′-IRES) region of HCV. Intracellular stability studies showed that the highest stabilization effects were obtained when the DNAzymes′ cores were jointly modified with 2′-C-methyl- and 2′-O-methylnucleosides, yielding an increase by up to fivefold in the total DNAzyme accumulation within the cell milieu within 48 h of transfection. Different regions of the HCV IRES were explored with unmodified 10–23 DNAzymes for accessibility. A subset of these positions was tested for DNAzyme activity using an HCV IRES-firefly luciferase translation-dependent RNA (IRES-FLuc) transcript, in the rabbit reticulocyte lysate system and in the Huh-7 human hepatocarcinoma cell line. Inhibition of IRES-dependent translation by up to 65 % was observed for DNAzymes targeting its 285 position, and it was also shown that the modified DNAzymes are as active as the unmodified one.